Les noms de sons et d’odeurs en russe. Valeurs et emplois - Thomières, Irina (Neophilologica, 2016)
The present paper examines in detail the predicative nouns of smell and of sound in contemporary Russian. It more specifically focuses on the structures ‘Noun of smell or odor + specifiers (“noun” in the genitive)’. The predicates mentioned are divided into groups according to the semantic nature of the specifiers: concrete noun, abstract noun, place name. They express the cause of the smell or sound. The features of each subset are described emphasizing the similarities and differences existing between the sounds on the one hand and the smells on the other.